Challenges of Combating Homegrown Terrorism in Kenya: A Youth Radicalization Perspective - Kariuki, Alice Mary Wamuyu (2019)
Radicalization and recruitment of young Kenyan males into homegrown terrorism has persisted since November 2011 following the decision by the government to send Kenya Defense Forces to fight al Shabaab terrorist groups in Somalia. Using Schneider and Ingram's conceptualization of social construction of target populations as a guide, the purpose of this multicase study was to explore the motivation of young Kenyan males in accepting radicalization and recruitment into homegrown terrorism and their interpretations, feelings, and perceptions of the policies and strategies in place to empower them. Using a purposeful sampling with a maximum variation strategy, data were collected through interviews with 34 young Kenyan males, 4 of whom were connected to 4 terrorism incidents in Kenya since 2011. Additional data were collected through publicly available data and policy statements. All data were inductively coded and subjected to a thematic analysis procedure and cross-case analysis. Findings indicated that young Kenyan males are enticed with financial offers by al Shabaab, and faced social problems that needed solutions, and participants believe the government of Kenya should better protect them from al Shabaab maneuvers. Implications for social change include recommendations for reform of youth policies and programs by the Ministry of Youth Affairs, and implementation of the recommendations of this study so that youth can be properly engaged in nation-building activities